(untitled) (Research, Society and Development, 2020)
One of the goals of nursing is health promotion, and because of that, the study of the environment, standing for the relationship between the professional and society, must be fully incorporated into nurses’ qualifications. This study aimed to analyze the insertion of environmental issues into a nursing degree in a middle-sized Brazilian city from the point of view of the different actors involved: professors, students, and coordinators. The study had a mixed-methods design. Data collection was done through a documentary analysis of political teaching projects; questionnaires to nursing students; and semi-structured interviews with coordinators and professors of Higher Education Institutions of the city. The quantitative data analysis was done through statistical methods and the Scott‒Knott Test; the qualitative data analysis was done through the content analysis proposed by Bardin. The results demonstrate a lack of proper handling of environmental issues, with the work only involving the specific environmental subjects that are the most prominent. Although environmental issues are only inserted at random into the teaching, the students still understand the importance of environmental knowledge as it applies to the technical subjects of the nursing degree.